Enhancing carrier generation in TiO2 by a synergistic effect between plasmon resonance in Ag nanoparticles and optical interference. Issue 32 (22nd July 2015) - Cacciato, Giuseppe; Bayle, Maxime; Pugliara, Alessandro; Bonafos, Caroline; Zimbone, Massimo; Privitera, Vittorio; Grimaldi, Maria Grazia; Carles, Robert
Abstract : Vibrations and electronic excitations are used as probes for carrier injection, light capture and SERS in Ag/TiO2 nano-composites. Abstract : Silver nanoparticles have been embedded at a few nanometer distance from the free surface of titania/silica multilayers using low energy ion beam synthesis. Transmission electron microscopy shows the presence of 3 nm-sized crystalline particles. Reflectance spectroscopy on these composite substrates shows an increase of the light capture efficiency in the visible range. This behaviour is interpreted as a synergistic effect between plasmon polariton resonance and Fabry–Perot interferences. Plasmon-resonant Raman spectroscopy is deeply used to analyze, on one hand confinement of vibrations and electronic excitations in Ag NPs, and on the other hand coupling of polar TiO2 phonons with injected photo-generated carriers. It is shown how these new Ag/TiO2 nanocomposite films appear as very promising to enhance the efficiency and enlarge the spectral sensitivity of plasmo-electronics devices.